Inequality in Public School Admission in Urban China Discourses, Practices and New Solutions - Liu, Jing (Education in the Asia-Pacific Region: Issues, Concerns and Prospects,, 2018)
This book explores and interprets discourses and practices in school admissions to public lower secondary education in urban China by utilizing a discourse analysis approach and a case study method. It identifies continuities and changes in discourses shaped by diverse forces in public lower secondary school admissions in the context of China's social transformation from a profit-driven society to a more equitable society, and elucidates the power relationships among stakeholders in public school admissions by analysing their interplay in the process. More importantly, it exposes how current socio-economic, institutional and educational systems are shaping the engagement of stakeholders in the public school admissions process. It also presents some on-going projects intended to yield new policies and practices for more equitable public secondary education in China in the development stage of the post-2015.